Millennials’ perception towards adaption and intention of m-banking: Experience from a developing country - Noman Hasan; Md. Shahed Mahmud; Abdul Khan; Reshma Lima; Shiblu Miah (Journal of Global Business Insights)
In recent years, m-banking has been developed rapidly around the world. The research aims to measure millennials’ perception towards adaption and intention of m-banking from a developing country’s perspective. A PLS-SEM modeling approach was performed to test the hypothetical model. The empirical results reveal that perceived ease of use, perceived security and privacy, and perceived cost significantly affect the millennials’ attitude to adopt m-banking. In contrast, perceived usefulness and perceived self-efficacy have an insignificant effect. Furthermore, attitude towards adopting m-banking significantly impacts adoption and intention among millennials. Practical and theoretical implications have been identified based on the study results.